Hypolipidaemic Effect of an Immature Pomelo (Citrus Maxima) Extract in a Tyloxapol-Induced Hyperlipidaemia Mouse Model - Pham, Ba Dien; Ton, Chi Nhan; Nguyen, Ngoc Chi Lan; Le, Minh Hoang (Scripta Medica, 2026)
BBackground/Aim: Pomelo extracts are rich in bioactive flavonoids and may regulate lipid metabolism. However, studies evaluating the lipid-lowering effects of immature pomelo derived from agricultural by-products remain limited in Vietnam. This study was conducted to investigate the hypolipidaemic activity of a liquid extract obtained from immature pomelo (Citrus maxima) in a tyloxapol-induced mouse model of acute hyperlipidaemia.Methods: Sixty mice were randomly assigned to six groups: normal control, pathological control (tyloxapol-induced hyperlipidaemia), positive control (atorvastatin-treated) and three experimental groups receiving immature pomelo extract orally at doses of 5.17, 10.34 and 15.51 g/kg. Key lipid indicators, including total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), were quantified in serum samples. Data were analysed using appropriate statistical tests, including the Shapiro–Wilk test, independent t-test and Levene’s test.Results: All extract doses significantly reduced total cholesterol, triglycerides and LDL-C compared with the pathological control (p < 0.001). The lowest dose produced the greatest reduction in total cholesterol (3.420 mmol/L), while higher doses showed stronger effects on HDL-C restoration, reaching levels similar to those recorded in the normal and atorvastatin-treated groups (2.100 and 1.950 mmol/L; p > 0.05)Conclusion: The liquid extract of immature pomelo demonstrated significant hypolipidaemic activity in this experimental model.
Keywords: Citrus maxima; Dyslipidaemia; Flavonoids; Hyperlipidaemia model; Tyloxapol